HUBUNGAN ANTARA ATRIBUT PRODUK TERHADAP KEPUTUSAN PEMBELIAN MINUMAN TEH DALAM KEMASAN - Widodo, Purwanto (Fakultas Pertanian Universitas Islam 45 (UNISMA) Bekasi, 2010)
This research intent to see influence of potion product attribute tea in pack to buy decision. Survey is arranged on year 2010 to 96 spread respondent at severally mall location that is at Bekasi's City. Of 96 respondents, apparently data which fledged 90 respondents. Result observationaling to point out that tea market compartment in pack at City Bekasi is: mature age rank, get male gender, education high enough, PNS'S circle work, swasta's clerk and wirausaha. Respondent income a large part among 500 thousand until with 4 million and a large part respondent have gotten married. According to respondent, tea in consumed pack: Price that is on the market by each relative's grocers is a steal, Ready tea to used or deep close-fitting pack for consumer. For consumer, to consumed is tea in expected pack will evoke freshness. Sharpness has permit from Depkes a thing that needs and they will look for its brand product was known. Largely respondent declare for tea buy place in pack is time business man five, swalayan's market supermarket and minimarket / is shop. Base trick decides buy a large part respondent declare for to outgrow abrupt, upon one at loose ends and wish overchanging and they the need. Price and brand variable constitute influential variable to tea buy decision bottle in pack.